2011
DOI: 10.1016/j.bmc.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

New vasorelaxant indole alkaloids, villocarines A–D from Uncaria villosa

Abstract: Villocarines A-D (1-4), four new indole alkaloids have been isolated from the leaves of Uncaria villosa (Rubiaceae) and their structures were elucidated by 2D NMR methods and chemical correlations. Villocarine A (1) showed vasorelaxation activity against rat aortic ring and showed inhibition effect on vasocontraction of depolarized aorta with high concentration potassium, and also inhibition effect on phenylephrine (PE)-induced contraction in the presence of nicardipine in a Ca(2+) concentration-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
(16 reference statements)
1
20
0
Order By: Relevance
“…These results suggested that rhynchophylline (32) and isorhynchophylline (40) exert antihypertensive activities by inhibiting of the vasomotor center, sympathetic nerves and ganglia and blocking of L-type decrease of calcium (Ca 2 þ ) channels (Song et al, 2000;Shi et al, 1989;Wang and Li, 1998;Zhang et al, 2004;Li et al, 2013); Villocarine A (10) and geissoschizine methyl ether (11) acted on rat aortic ring to show vasorelaxation activities. The underlying mechanisms of villocarine A (10) mainly described as follows: (i) inhibited calcium influx from extracellular space through voltage-dependent calcium channels and/or receptor-operated Ca 2 þ -channels; (ii) promoted the release of NO from endothelial cells; (iii) stimulated the opening of voltage-gated K þ -channels (Matsuo et al, 2011). Different from villocarine A (10), geissoschizine methyl ether (11) affected aortic ring through endothelial dependency with nitric oxide at low concentrations of 0.1-3 mM and endothelial independency with Ca 2 þ channel blockade at higher concentrations of 10-100 mM (Yuzurihara et al, 2002).…”
Section: Antihypertensionmentioning
confidence: 99%
“…These results suggested that rhynchophylline (32) and isorhynchophylline (40) exert antihypertensive activities by inhibiting of the vasomotor center, sympathetic nerves and ganglia and blocking of L-type decrease of calcium (Ca 2 þ ) channels (Song et al, 2000;Shi et al, 1989;Wang and Li, 1998;Zhang et al, 2004;Li et al, 2013); Villocarine A (10) and geissoschizine methyl ether (11) acted on rat aortic ring to show vasorelaxation activities. The underlying mechanisms of villocarine A (10) mainly described as follows: (i) inhibited calcium influx from extracellular space through voltage-dependent calcium channels and/or receptor-operated Ca 2 þ -channels; (ii) promoted the release of NO from endothelial cells; (iii) stimulated the opening of voltage-gated K þ -channels (Matsuo et al, 2011). Different from villocarine A (10), geissoschizine methyl ether (11) affected aortic ring through endothelial dependency with nitric oxide at low concentrations of 0.1-3 mM and endothelial independency with Ca 2 þ channel blockade at higher concentrations of 10-100 mM (Yuzurihara et al, 2002).…”
Section: Antihypertensionmentioning
confidence: 99%
“…Villocarine showed slightly less vascular relaxation activity in aortic tissues with no endothelium. Villocarine A was isolated from Uncaria villosa ( Figure 11 ) [ 39 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The structures of 1 – 4 were elucidated by 1D and 2D NMR, UV, MS, and circular dichroism (CD) techniques, and 5 – 11 were identified by comparing their 1 H NMR, UV, MS, and CD data with reported values [8–10]. Compound 1 was confirmed as a new alkaloid, 4-geissoschizine N -oxide methyl ether (1) , together with the following 10 known alkaloids 3-epi-geissoschizine methyl ether (2) isolated from U. rhynchophylla for the first time [11], geissoschizine methyl ether (3) , 4-hirsuteine N -oxide (4) , hirsuteine (5) , hirsutine (6) , 3α-dihydro-cadambine (7) , 3β-isodihydro-cadambine (8), cadambine (9) , strictosamide (10) , and akuammigine (11) . The neuroprotection of 1 – 9 against glutamate-induced HT22 cell death was assayed for the first time.…”
Section: Resultsmentioning
confidence: 99%